Androgen receptor enhancer amplification in matched patient‐derived xenografts of primary and castrate‐resistant prostate cancer. Issue 2 (29th March 2021) - Porter, Laura H; Bakshi, Andrew; Pook, David; Clark, Ashlee; Clouston, David; Kourambas, John; ,; Goode, David L; Risbridger, Gail P; Taylor, Renea A; Lawrence, Mitchell G
Abstract: Amplifications of the androgen receptor (AR) occur in up to 80% of men with castration‐resistant prostate cancer (CRPC). Recent studies highlighted that these amplifications not only span the AR gene but usually encompass a distal enhancer. This represents a newly recognised, non‐coding mechanism of resistance to AR‐directed therapies, including enzalutamide. To study disease progression before and after AR amplification, we used tumour samples from a castrate‐sensitive primary tumour and castrate‐resistant metastasis of the same patient. For subsequent functional and genomic studies, we established serially transplantable patient‐derived xenografts (PDXs). Whole genome sequencing showed that alterations associated with poor prognosis, such as TP53 and PTEN loss, existed before androgen deprivation therapy, followed by co‐amplification of the AR gene and enhancer after the development of metastatic CRPC. The PDX of the primary tumour, without the AR amplification, was sensitive to AR‐directed treatments, including castration, enzalutamide, and apalutamide. The PDX of the metastasis, with the AR amplification, had higher AR and AR‐V7 expression in castrate conditions, and was resistant to castration, apalutamide, and enzalutamide in vivo . Treatment with a BET inhibitor outperformed the AR‐directed therapies for the metastasis, resulting in tumour regression for some, but not all, grafts. Therefore, this study provides novel matched PDXs to test potential treatments that target the overabundance of AR in tumours with AR enhancer amplifications. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.